RANCANG BANGUN DESAIN STAND PKL NGARSOPURO BERBASIS ERGOKULTURAL DENGAN PEMANFAATAN LIMBAH KAYU PALET - Utomo, Tri Prasetyo; Mardjono, M., (Institut Seni Indoensia Surakarta, 2017)
Stand product is an important tool that is used to support the smooth operation of the business in thepublic space for entrepreneurs. Stand product used by employers to display merchandise products inorder to attract visitors to come and make transactions, so as to increase the income of smallentrepreneurs.This applied research aims to determine the condition of the product PKL Stand NightMarket Ngarsopuro, then perform analysis and sinteta, then do engineering design in accordancewith ergonomic aspects and kulural. Stand so that there can function optimally support the view theproducts offered, to increase sales turnover PKL. Give a touch of local culture so that tourists whocome to identify with both local content in Surakarta. Creation of art / design endeavors to utilizewood waste material discarded packaging / pallets which are found in Surakarta container terminalto be used again. Applied research objects of art / design is PKL Stand Night Market Ngarsopuro, themethods used in descriptive qualitative approach supported by quantitative data, or can also becalled dual research strategy. Kuantitafif here using numerical data which is the result of the measurement field, and then compared with the reference referred, sources and analyzed by researchersinterpretation. Activities beginning with product discovery phase to obtain a result of the creation ofinnovations in product design process.The results of applied research art / design show that the standthat there is now not yet meet the standards of ergonomics and yet showed a touch of culture. Furthermore, in this study, the design of booths in accordance with the standards of ergonomics and cultural.Keywords: stand products, ergokultural, wood waste.